Attitudes of Clinicians Towards Euthanasia and Physician-Assisted Suicide in Terminally Ill Patients - Dar, Kamran Mahmood; Ahmed, Salman; Hussain, Mansoor (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine attitudes of clinicians involved in care of terminally ill patients towards euthanasia and physician-assisted suicide (PAS). Study Design: Descriptive cross-sectional study. Place and Duration of Study: Military Hospital (MH), Combined Military Hospital (CMH) and Armed Forces medical institutes in Rawalpindi, Pakistan, from Jul 2019 to Jan 2020. Methodology: Clinicians were asked to answer a self-administered questionnaire which was then collected and all data was analysed by Statistical Package for the Social Sciences (SPSS) version 21.00. Both descriptive statistics and inferential statistics were used for comparing respondents, according to age, gender, religion, marital status, speciality, qualification, job designation, hospital, clinical experience, and any clinical experience abroad, regarding their attitudes towards euthanasia. Results: Out of 60 clinicians, 55(91.70%) had negative attitude while 5(8.30%) had positive attitude towards euthanasia and physician-assisted suicide, 53 clinicians (88.30%) were male and 7(11.70%) were female. All were Muslims and 48 doctors (80.00%) had clinical experience abroad while 56 clinicians (93.30%) were married and 4(6.70%) were unmarried. Most of the married doctors had negative attitude towards euthanasia as compared to unmarried ones. (94.60% vs. 50.00%) Conclusion: Most of the clinicians involved in care of terminally ill patients had negative attitudes towards euthanasia and physician-assisted suicide.